2018
DOI: 10.1111/ppl.12719
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis ofGlycine sojaubiquitin (UBQ) genes and functional analysis ofGsUBQ10in response to alkaline stress

Abstract: Ubiquitin is a highly conserved protein with multiple essential regulatory functions through the ubiquitin-proteasome system. Even though its functions in the ubiquitin-mediated protein degradation pathway are very well characterized, the function of ubiquitin genes in the regulation of the alkaline stress response is not fully established. In this study, we identified 12 potential UBQ genes in the Glycine soja genome, and analyzed their evolutionary relationship, conserved domains and promoter cis-elements. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The photosynthetic rate, sugar production, N metabolism and amino acid production were also significantly inhibited under alkaline stress (at high pH) (Hu et al, 2015). Further, alkaline stress has affected 434 million ha of land and limited the crop productivity worldwide (Chen et al, 2018), although single form of soybean SOD gene has been identified under various stresses (Gopavajhula et al, 2013;Wang et al, 2016). It is necessary to explore the roles of soybean SOD family under environmental stresses, especially under alkaline stress.…”
Section: Introductionmentioning
confidence: 99%
“…The photosynthetic rate, sugar production, N metabolism and amino acid production were also significantly inhibited under alkaline stress (at high pH) (Hu et al, 2015). Further, alkaline stress has affected 434 million ha of land and limited the crop productivity worldwide (Chen et al, 2018), although single form of soybean SOD gene has been identified under various stresses (Gopavajhula et al, 2013;Wang et al, 2016). It is necessary to explore the roles of soybean SOD family under environmental stresses, especially under alkaline stress.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean UBQs were also involved in stress responses. However, unlike in rice, overexpression of GsUBQ10 in alfalfa significantly improved the alkaline tolerance, and soybean UBQ10 plays a positive role in responses to alkaline stress (C. Chen et al., 2018). GmBTB/Zinc finger of poxvirus (POZ), a novel Broad‐complex、Tramtrack and Bric‐abrac (BTB)/POZ domain‐containing nuclear protein, was located in the cell nucleus and up‐regulated by P. sojae , functions as a positive regulator in the soybean response to P. sojae infection (C. Zhang et al., 2019): The GmBTB/POZ interacts with GmAP2 and GmLHP1 to regulate the defense response to P. sojae .…”
Section: Role Of the Ubiquitin‐proteasome System In Soybean Yieldmentioning
confidence: 99%
“…GmAP2 and GmLHP1‐RNAi exhibited enhanced resistance to P. sojae (Zhang, Cheng et al., 2021). In addition, GmSK1 might play a role in the crosstalk between ubiquitination and drought and salt stress responses (Y. P. Chen et al., 2018) (Table 1).…”
Section: Role Of the Ubiquitin‐proteasome System In Soybean Yieldmentioning
confidence: 99%